Profil Capaian Iklim Kebhinekaan Jenjang Sekolah Dasar di Provinsi NTB Berbasis Rapor Pendidikan 2023 - Ardiansyah, Bakhtiar (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research aims to provide an overview regarding the map of educational quality achievements, especially the climate of diversity at the elementary school level throughout NTB Province using the Education Report Card database issued in 2023. This research is descriptive research with data reduction methods. The data source uses educational report card achievement data, especially diversity climate achievements in each district/city throughout NTB Province as well as documentation from the Character Strengthening Center and several educational units in NTB Province.  The research results provide information that the majority of educational units are in the Good category (57.86% to 91.57%). Most also experienced an increase in achieving a climate of diversity.